Effective fuel temperature of WWER-1000; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Kudrov A. I. Alexander Ivanovich (2017, 2017)
Title screen